The proficiency of english reading comprehension level developed by the students while Taking English I, in the Bachelor in Chemistry at the School of Natural Sciences and Mathematics, University of El Salvador, semester I, year 2019 - Artero Ruiz, Marina del Rosario; Candelario de Vásquez, Ruth Marjorie; Ramírez Monge, Karina Yamileth; Mata Chávez, Miguel Ángel; Contreras Cárcamo, Mauricio Salvador (San Salvador , El Salvador : Universidad de El Salvador., 2019)
This study is focused on how effective the proficiency of English reading comprehension level that students develop while taking English I at the School of Chemistry, University of El Salvador, semester I, the year 2019 is. This research work is conducted through a qualitative and quantitative approach. The theoretical part contains previously conducted studies related to the issue with available literature sources focus particularly on English in Natural Sciences. The Chemistry students will Answer questionnaires, and taking reading tests twice. Therefore, the research practitioners will administer a semi-structured interview to the teacher, and an observational guide for checking the teacher’s performance. The data will be collected through four different instruments: questionnaires, reading comprehension tests, semi-structured interview addresses to the teacher, and a classroom observational guide. The readings comprehension tests will be scored and the data will be analyzed in an interval scale with the ACTFL guidelines, the statistical procedure will be developed through graphs. The semi-structure interview will be analyzed and described. The classroom observational guide will be analyzed and presented and the questionnaires will be presented as well.
Bibliografia : hojas 82-84
Keywords: Inglés -- Enseñanza